CONTEMPORARY TEACHING METHODOLOGY OF ENGLISH FOR STUDENTS - Khidoyatova Shakhlo (Journals Park Publishing, 2022)
This article provides detailed information about modern and innovative methods of teaching English in the 21st century. The article describes methods and innovative methods aimed at identifying and solving some problems related to language learning among students in schools, and developing their language skills. These methods, innovative methods and information technologies significantly enrich English language teaching.
Keywords: innovative methods, modern technologies, students, English, interest, communicative approach, interactive games, practical lessons.